Someone makes videos and gets the money for it’ - Agency of Older TikTokers in Digital Capitalism - Edit, (Magyar Gerontológia, 2025)
The capitalist operations of today have been described in various forms in literature, and while each concept highlights different aspects of this operation, they all agree that large tech companies are the biggest beneficiaries of this transformation, capable of influencing market dynamics and consumer behaviour.